Penyuluhan Kesehatan Perawatan Pasca Khitan - Arif Hendra Kusuma; Budi Priyanto (JPS : Jurnal Pengabdian Serulingmas, 2021)
There are still many parents who do not know what to do after their child undergoes circumcision, especially regarding treatment for wound healing. The belief to abstain from eating after the circumcision process with the aim of getting circumcised wounds to heal quickly is still widely held by the community, especially by parents. Children usually obey what their parents say. Parents should know what to do after their child is circumcised, both for the treatment and nutrition needed for wound healing. The purpose of this activity is to increase the knowledge and skills of parents regarding post circumcision care. The method used in this community service is health counseling and the correct management of the use of drugs. The target in this activity is parents whose children participate in mass circumcision at MAN 1 Cilacap which amounted to 13 people. The results of the activity were an increase in the knowledge and skills of parents regarding post-circumcision care and the correct use of drugs.